Information Jockey: The Dubious Role of the 21st-century Academic - Haahr, Mads (My University, 2002)
While the university has traditionally been our primary centre for the management of knowledge, a variety of factors are changing the processes associated with this function. This paper discusses the university’s transition from industrial to information society by focusing on the four processes of knowledge advancement, transmission, preservation and diffusion and the way these processes are shaping (and being shaped by) current advancements in information technologies. Particular attention is given to the fact that many trends indicate a shift in the role of the academic towards a stronger focus on the consumption, recombination and dissemination of information rather than the reflection arguably required for the creation of new knowledge.
PUBLISHED